A gestão por competências como política governamental para o desenvolvimento turístico de municípios do brejo paraibano - Navarro, Arthur Martins Marques (2019)
The objective of this study was to propose guidelines for the implementation of competence-based management as a government policy for the tourist development of municipalities in the Brejo Paraibano region. Initially, a theoretical foundation was developed to base the study, addressing the following topics: Municipal Management, Territorial Development, Competence Management, Origin and evolution of the meaning of Competence Management, Competence-Based Management in the Public Sector and Competence-Based Management in municipalities: An approach under construction. The proposal was based on a multi-level approach, with competence-based management covering the regional level (competences of a region that integrates a territory), the municipal level (competences necessary for excellence in municipal management) and the individual level (competences of managers and municipal civil servants). The research is qualitative and exploratory and descriptive in nature It was carried out in the municipalities of Areia, Alagoa Grande, Bananeiras and Pilões, through semi-structured interviews with managers, employees, presidents of regional associations, directors of university academic centers in the region surveyed, mayors, former mayors, secretaries and municipal directors, i.e., addressing the three levels of research. Observation and documentary analysis were also used to collect data. The results of the research were achieved through the content analysis of Bardin (2011) and were presented following the proposal of levels and the main categories identified: Regional Level: Regional Integration, Partnerships and Infrastructure. Municipal Level: Planning and Financial Resources and Individual Level: Management Professionalization. Based on the categories that emerged, the following guidelines were proposed: Creation of the Intermunicipal Consortium for the Development of the Brejo Paraibano - ICDBP, Preparation of a Strategic Plan for Developing the Brejo Paraibano - SPDBP, Competence Mapping and a Competence Based System of Training and Appointment for Commissioned Servants. In the end, it is concluded that the proposal of a new approach to professionalize the management of municipalities is challenging because it involves a multi-level perspective of analysis and has potential for the development of the municipalities and of the region where they are inserted.